2021
DOI: 10.33448/rsd-v10i14.21878
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of acetic fermentation with different fruit peels

Abstract: Acetic fermentation or vinegar is the product obtained from fermented alcoholic wort, cereals or hydroalcoholic mixture with a minimum volatile acidity of 4g/100m.L-1. The present study produced, characterized and correlated the total dry extract with the density of the acetic fermented produced from the pineapple and apple peels. The fermentation process used pineapple and apple peel with culture medium, 10% hydroalcoholic solution, room temperature between 28 ± 2°C and irrigation 4 (four) times a day, withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Different contents of total dry extract in fruit peel vinegar have been reported in the literature. Prisacaru et al 49 reported values ​​between 2.11 g/100 mL and 26.43 g/100 mL, while values between 6.90 g/L and 10.59 g/L were mentioned by 50 . The Brazilian legislation determines a minimum amount of 6 g/L of reduced dry extract in fruit vinegars, the values ​​found in the present work within the current legislation limit.…”
Section: Resultsmentioning
confidence: 98%
“…Different contents of total dry extract in fruit peel vinegar have been reported in the literature. Prisacaru et al 49 reported values ​​between 2.11 g/100 mL and 26.43 g/100 mL, while values between 6.90 g/L and 10.59 g/L were mentioned by 50 . The Brazilian legislation determines a minimum amount of 6 g/L of reduced dry extract in fruit vinegars, the values ​​found in the present work within the current legislation limit.…”
Section: Resultsmentioning
confidence: 98%
“…Different contents of total dry extract in fruit peel vinegar have been reported in the literature. Prisacaru et al 44 reported values between 2.11 g/100 mL and 26.43 g/100 mL, while values between 6.9 g/L and 10.59 g/L were mentioned by 45 . The Brazilian legislation determines a minimum amount of 6 g/L of reduced dry extract in fruit vinegars, the values found in the present work are in accordance with the current legislation.…”
Section: Fermentation Parametersmentioning
confidence: 98%
“…Although there are not many studies in the literature about these traditional fermented beverages, it is known that the use of fruit during the fermentation process of beverages such as beer enhances the content of bioactive compounds, in particular polyphenols and carotenoids [86]. Acetic fermentation to obtain vinegar is also a popular process to give additional uses to many fruit wastes [83]. Traditionally associated with wine, vinegar can be produced from many fruit wastes such as the peels and cores from apple, kiwi fruit, pineapple, pear, mango, melon, watermelon, etc.…”
Section: Dietary Uses Of Fruit and Vegetable Wastementioning
confidence: 99%